The Uk Electricity Market Evolution During the Liberalization Process - Delia Vasilica Rotaru (CES Working Papers, 2013)
This paper offers an insight on the liberalization process that took place in the United Kingdom starting with 1990 until now. The electricity market in the United Kingdom made incredible progress in the road to reaching a full level of liberalization where customers are free to choose between suppliers and services. An analysis of the most important indicators for the electricity market evolution such as electricity price, the market share of the largest generator, the energy efficiency indicator shows that the liberalization process brought many advantages starting with 2001. Also, UK has to face new challenges in order to keep the development of the industry on the right path, challenges that are presented in the final part of the paper.
Keywords: L16; L94; Q43; 330; UK electricity market; liberalization; energy efficiency; deregulation; market structure Romania